Analysis of strategies to decarbonise the UK housing stock - Sousa Ramírez, Gustavo Alfonso (2017)
The purpose of this Thesis is to revise the adoption of strategies for both new and existing housing towards the reduction of carbon emissions associated to energy demand, particularly by identifying promising technical improvements, as well as by capturing potential incentives to adopt these improvements. The case of housing is particularly interesting because although it is straightforward to categorise each building, perhaps by its physical properties, it can be considered unique because of the quasi-random behaviour of their occupants which can be determined as collective (e.g. peer pressure influencing the installation of solar panels), circumstantial (e.g. local incentives or sales in efficient devices), biological (e.g. occupants needs according to age and health conditions), or cultural (e.g. habits and patterns). It is also interesting because domestic buildings—or dwellings—represent a starting point in which our decisions to improve energy demand are taken, specially because these are biased by the exercise of rights and privileges, which do not necessarily comply with inhabitant’s comfort and satisfaction.